Coordination polymer based perovskite device: matched energy levels and photocurrent enhancement in the absence or presence of methanol. Issue 46 (13th November 2017) - Lv, Sen; Wang, Zhe Yuan; Gu, Xu; Zhang, Chong; Gong, Yun; Lin, Jian Hua
Abstract : A coordination polymer based perovskite device yielded much larger photocurrent density with or without methanol under visible light illumination, which is ascribed to their matched VBM/CBM energy levels. Abstract : Using 3, 6, 3′-biphenyltricarboxylic acid (H3 L1 ) and N 1, N 4 -di(pyridin-4-yl)terephthalamide (L ), two coordination polymers (CPs) formulated as Co3 L2 (L1 )2 (H2 O)8 ·3H2 O (1 ) and ZnL0.5 (HL1 )(H2 O)·2H2 O (2 ) have been hydrothermally synthesized and structurally characterized by single-crystal X-ray diffraction. CP2 exhibits a uninodal 3-connected two-dimensional (2D) framework with 6 3 -hcb topology and DFT calculation reveals that it is a semiconductor. CP2 shows photocurrent response under visible light illumination (650 nm > λ > 350 nm). Based on CP2, a device based on FTO/TiO2 /perovskite CH3 NH3 PbI3 /CP2 was constructed, which yielded a much larger photocurrent density than CP2 in aqueous electrolyte solution under visible light illumination (650 nm > λ > 350 nm), and it is ascribed to the matched valence-band maximum (VBM) and conduction-band minimum (CBM) energy levels of CP2 and CH3 NH3 PbI3 . In the presence of methanol, the photocurrent response generated on the device can be remarkably improved, which is due to the photoinduced holes captured by methanol, leading to the more efficient separation of the photoinduced electrons and holes.